Inhibitory Effects of 4-(4-Methylbenzamino)benzoate on Adipocyte Differentiation. (1st October 2015) - Hwang, Jin Taek; Kim, Sanghee; Yoon, Bo-ra; Choi, Inwook; Choi, Sang Yoon
Abstract : The potent suppression of adipocyte differentiation by 4-(4-methylbenzamino)benzoate was discovered during the search for new antiobesity compounds. 4-(4-methylbenzamino)benzoate was observed to suppress adipocyte differentiation in 3T3-L1 cells by 96.8% at 50 μ M without cytotoxicity. In addition, 4-(4-methylbenzamino)benzoate reduced the cellular expression of fatty acid synthase in a concentration-dependent manner, as well as suppressing PPAR-gamma activity, which controls fatty acid storage and glucose metabolism. Based on these results, 4-(4-methylbenzamino)benzoate shows potential as an antiobesity material.